(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The current research aimed to find out the types of floor finishes used in temporary housing during the pilgrimage season to the holy places (Najaf and Karbala) and the extent of their impact on visitors from a health standpoint. It also sought to identify the barriers to the non-sustainability of internal space floors made of environmentally friendly materials, which has a positive impact on environmental and functional health. On the study sample, the study used an analytical descriptive technique (30 tents). The investigation came to the following conclusions: 1- There is a statistically significant relationship between the visitor’s health status and the floor of temporary housing in the holy places. 2- There is a statistically significant link between unsustainable flooring practices 3-There is a favorable and statistically significant association between the durability of the temporary housing’s floors and its practical and aesthetically pleasing features. Among the study’s most crucial recommendations: • The study advocated utilizing the interior designer’s expertise to develop interior environments that satisfy societal and individual demands while also achieving the aesthetic, practical, and financial goals of the interior spaces. 2. Promoting sustainable green interior design that not only serves to minimize pollution but also doesn’t impact the surrounding environment.